2016
DOI: 10.1103/physrevb.94.054508
|View full text |Cite
|
Sign up to set email alerts
|

Competing effects of Mn and Y doping on the low-energy excitations and phase diagram ofLa1yYyFe1xMnx

Abstract: Muon Spin Rotation (µSR ) and19 F Nuclear Magnetic Resonance (NMR) measurements were performed to investigate the effect of Mn for Fe substitutions in La1−yYyFe1−xMnxAsO0.89F0.11 superconductors. While for y = 0 a very low critical concentration of Mn (x = 0.2%) is needed to quench superconductivity, as y increases the negative chemical pressure introduced by Y for La substitution stabilizes superconductivity and for y = 20% it is suppressed at Mn contents an order of magnitude larger. A magnetic phase arises … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…14,15 Interestingly, the partial substitution of La with smaller Y ions drives the system away from quantum criticality, implying that a higher chemical pressure reduces the effects of Mn magnetic correlations. 16 It is conceivable that the same mechanism, i.e., a higher chemical pressure, reflecting the smaller size of Sm ions, can explain why T c decreases more slowly in the Sm-1111 than in La-1111 compounds for nominally equal Mn contents. 6 Although a higher chemical pressure implies weaker electronic correlations, these still persist and have been shown to enhance the inter-impurity Ruderman-Kittel-Kasuya-Yosida (RKKY) exchange interaction, responsible for the competition between the magnetically-ordered and the superconducting phase.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Interestingly, the partial substitution of La with smaller Y ions drives the system away from quantum criticality, implying that a higher chemical pressure reduces the effects of Mn magnetic correlations. 16 It is conceivable that the same mechanism, i.e., a higher chemical pressure, reflecting the smaller size of Sm ions, can explain why T c decreases more slowly in the Sm-1111 than in La-1111 compounds for nominally equal Mn contents. 6 Although a higher chemical pressure implies weaker electronic correlations, these still persist and have been shown to enhance the inter-impurity Ruderman-Kittel-Kasuya-Yosida (RKKY) exchange interaction, responsible for the competition between the magnetically-ordered and the superconducting phase.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, while in most the IBS compounds the T c suppression rate (dT c /dx) is well below 10 K/% Mn, in LaFeAsO 0.89 F 0.11 just 0.2 -0.3% of Mn impurities suppress superconductivity from the optimal T c 27 K (dT c /dx ∼ 110 K/% Mn) and then, at higher Mn doping levels, a magnetic order develops (see Fig. 1b) [32][33][34]. The understanding of why such a dramatic effect is present, what type of magnetic order is developing and how to describe these materials at the microscopic level are presently subject of debate [35][36][37].…”
mentioning
confidence: 99%
“…Previous experimental results have shown that this system can be driven away from the QCP via the total substitution of La with Nd or by the partial substitution with Y [33,34], which shrink the structure and cause a reduction of the electronic correlations [27]. Hence, the Ln1111 compound can be considered as a formidable example of how the electronic properties of strongly correlated systems can be significantly affected by fine-tuning the correlation strength with impurities and chemical pressure.…”
mentioning
confidence: 99%
“…Recently it was shown that Y-substitution for La can similarly shift OD La-1111 away from the QCP and remove the poisoning effect. [27] Non-magnetic disorder. We now turn to the discussion of non-magnetic disorder, and again motivate the study by a set of puzzling experimental findings from FeSCs summarized in Figs.…”
mentioning
confidence: 99%